Strategi Penegakan Hukum Internasional Dalam Menanggulangi Perdagangan Narkotika Lintas Negara Melalui Jalur Maritim - Aurelita, Mira; Prasetyo, Handoyo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The era of globalization accompanied by technological advances and connectivity between countries opens opportunities for the development of transnational crimes, one of which is narcotics trafficking. In recent years, the global narcotics trade has undergone a significant shift. International syndicates have begun to utilize maritime and water routes as the main distribution route, shifting the focus from the previously dominant land route. This research aims to find out what factors cause the large number of transnational narcotics trafficking through maritime routes and how a comprehensive and integrated international law enforcement strategy to tackle narcotics trafficking through maritime routes. This type of research is normative juridical with a statutory approach and case approach, as well as a literature study method. The result of this research is that factors such as ease of access, sophisticated technology, weak supervision, and economic factors provide a wide gap for drug traffickers. International legal instruments such as UNTOC and the 1988 UN Convention provide a foundation for cooperation and maritime law enforcement. However, high levels of state commitment and close international cooperation are required to overcome these challenges.